2017
DOI: 10.1111/pce.13028
|View full text |Cite
|
Sign up to set email alerts
|

Virulence determines beneficial trade‐offs in the response of virus‐infected plants to drought via induction of salicylic acid

Abstract: It has been hypothesized that plants can get beneficial trade-offs from viral infections when grown under drought conditions. However, experimental support for a positive correlation between virus-induced drought tolerance and increased host fitness is scarce. We investigated whether increased virulence exhibited by the synergistic interaction involving Potato virus X (PVX) and Plum pox virus (PPV) improves tolerance to drought and host fitness in Nicotiana benthamiana and Arabidopsis thaliana. Infection by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
95
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(105 citation statements)
references
References 76 publications
9
95
1
Order By: Relevance
“…Aguilar et al () have expanded on previous studies by examining drought resistance in N. benthamiana plants following infection with plum pox virus (PPV, the causative agent of Sharka disease in Prunus spp. : Damsteegt et al, ), potato virus X (PVX), a genetically engineered PPV recombinant expressing the PVX RNA silencing suppressor molecule P25 (PPV‐P25), and mixed PPV/PVX infection.…”
Section: Salicylic Acid: a Role In Virus‐induced Drought Resilience?mentioning
confidence: 99%
See 2 more Smart Citations
“…Aguilar et al () have expanded on previous studies by examining drought resistance in N. benthamiana plants following infection with plum pox virus (PPV, the causative agent of Sharka disease in Prunus spp. : Damsteegt et al, ), potato virus X (PVX), a genetically engineered PPV recombinant expressing the PVX RNA silencing suppressor molecule P25 (PPV‐P25), and mixed PPV/PVX infection.…”
Section: Salicylic Acid: a Role In Virus‐induced Drought Resilience?mentioning
confidence: 99%
“…They also examined the effects of PPV, PPV‐25, and PPV/PVX mixed infections on drought resistance in A. thaliana (note that PVX alone is not able to infect this host: Brosseau & Moffett, ). In all cases it was found that virus infection could to some extent relieve the symptoms of drought (Aguilar et al, ).…”
Section: Salicylic Acid: a Role In Virus‐induced Drought Resilience?mentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses have been shown to enhance drought tolerance through the promotion of salicylic acid (SA) signalling (Aguilar et al , ). C4‐expressing plants, however, do not overaccumulate SA and do not display increased expression of SA marker genes (data not shown), indicating that the events underlying the effect of C4 on drought stress tolerance are different to the ones previously described for other viruses (Aguilar et al , ; Westwood et al , ; Xu et al , ).…”
mentioning
confidence: 99%
“…Plants have adopted a wide range of strategies to confront the negative effects of drought, including increasing water uptake by optimizing the root system, closing stomata to limit the water loss caused by transpiration, accumulating osmoprotectants, or producing the hormone abscisic acid (ABA). This intricate scenario makes drought resistance a highly complex trait, with polygenic nature, low heritability, and vastly influenced by genotypeenvironment interactions (Fang and Xiong, 2014).A growing body of evidence indicates that viral infections can result in improved plant tolerance to abiotic stresses (see, among others: Aguilar et al, 2017;Anfoka et al, 2016;Westwood et al, 2012;Xu et al, 2008), raising the tantalizing idea that the identification of the molecular mechanisms underlying these viral effects could unlock yet-unknown stress tolerance strategies and pave the way for the generation of stress-resilient plants. Geminiviruses are viruses with small circular, single-stranded DNA genomes that infect a broad range of plants.…”
mentioning
confidence: 99%